Ultrasound measures of abdominal fat layers correlate with metabolic syndrome features in patients with obesity - Guillem Cuatrecasas; Francisco deCabo; Maria Josep Coves; Ioana Patrascioiu; Gerardo Aguilar; Sonia March; Mariona Balfegó; Clara Bretxa; Marta Calbo; Gabriel Cuatrecasas; Gloria Aranda; Aida Orois; et al. (Wiley, 2020)
Summary Objective Abdominal fat ultrasound (US) is a simple clinical tool that may allow measures of fat depots not visible using common dual‐energy X‐ray absorptiometry (DEXA) or computerized tomography (CT) imaging. The aim of this study was to validate the technique, give measures of superficial and profound subcutaneous, preperitoneal, omental and perirenal (retroperitoneal) fat and correlate them with MS markers. Methods Sequential US measures of these five abdominal fat layers were done at 397 adults. Blood pressure (BP), body mass index (BMI), waist, body fat %, HOMA‐IR index (homeostatic model assessment of insulin resistance), lipid profile and leptin were recorded. Metabolic syndrome (MS) was defined according to Cholesterol education programme adult treatment panel III (ATPIII) criteria. Results Subcutaneous and omental fat were increased among people with obesity, whereas preperitoneal and perirenal fat did not show any difference according to BMI or waist. Women showed thicker subcutaneous fat (both superficial and profound), whereas men had bigger omental fat. Both postmenopausal and diabetic patients had changes in omental fat only, whereas patients with fatty liver showed thicker preperitoneal and perirenal fat, as well. MS patients showed both thicker perirenal and omental fat. A cut‐off of 54 mm in male (M)/34 mm in female (F) of omental fat and 22.5 mm (M)/12.5 mm (F) of perirenal fat could be predictive of later MS onset. Conclusions US is a valid method to measure all different abdominal fat depots. Omental and perirenal fat measures may classify patients at risk for MS. Preperitoneal fat depot may also correlate with fatty liver disease.